Transcatheter closure of atrial septal defect with atrial septal occluder in a patient with nickel allergy - Hasan Arı; Selma Arı; Ahmet Tütüncü; Alper Karakuş; Mehmet Melek (KARE Publishing, 2017)
Presently described is transcatheter closure of atrial septal defect with atrial septal occluder (ASO) device in a patient with nickel allergy. Patients with metal allergy who will undergo nitinol device implantation should be tested for possible nickel hypersensitivity. ASO device and treatment strategy (percutaneous or surgical) should be selected according to allergy test result.